Trauma fisario en la edad pediátrica, una descripción histórica de su clasificación - Martínez Estupiñan, Lázaro Martín; Martínez Aparicio, Láraro; martínez Aparicio, Leonardo (Mediciego, 2022)
Introduction: the classification of physeal lesions in the history of traumatology goes through many tendencies and authors. At present they still constitute a source of controversy among specialists. Objective: to describe the historical development of the classifications for traumatic injury of the physis. Methods: a systematic bibliographic review of the classifications related to traumatic epiphysiolysis in the immature skeleton was carried out. The analytical-synthetic, historical-logical and inductive-deductive theoretical methods were used. Articles published in PubMed, in Spanish and English, were consulted and articles accessible freely or through ClinicalKey and Hinari were examined. Some that exceed five years old were taken into account, but that were key in the historical evolution of the subject. Development: Immature bone fractures account for 15 % of all injuries during childhood. The essential anatomophysiological, epidemiological, biomechanical, clinical and surgical details that supported the classifications and typologies that have transcended to the present are described. It was in the middle of the 20th century the stage of greatest boom with three classifications. However, the Salter and Harris classification of 1963, which included approximately a third of skeletal injuries in children, continues to be valid in the world and in Cuba, as it provides an excellent guide for the treatment and prognosis of the patient. Conclusions: there are multiple classifications and typologies of traumatic physeal injury, in Cuba the most used is that of Salter and Harris.